HUBUNGAN ANTARA BEBAN KERJA DENGAN STRESS KERJA ANGGOTA DITLANTAS POLDA SUMATERA SELATAN - Oktaviana, Rina; Muhammad Candra Ilham (Bajang Institute, 2024)
This study aims to determine the Relationship Between Workload And Job Stress Members of Polda The South Sumatra. The hypothesis proposed in this study is that there is a Relationship Between Workload And Job Stress Members of Polda The South Sumatra. The population in this study was 127 members of Polda were used as samples. The sampling technique used simple random sampling technique. The measuring instrument used in this study is the workload scale and the job stress scale. The analysis technique uses a simple regression analysis technique with the help of SPSS version 20. The results of the analysis of research data using a computer using the SPSS version 20 for windows program, show the correlation coefficient (r) of 0.634, the coefficient of determination (R Square) of 0.402, and the value of p = 0.000. The results of the analysis obtained show that there is a very significant relationship between workload and job stress members of Polda The South Sumatra by 40,2%.